2007
DOI: 10.1111/j.1939-1676.2007.tb02953.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Adrenal Insufficiency in Dogs with Sepsis

Abstract: Delta-cortisol < or = 3 microg/dL after adrenocorticotropic hormone administration is associated with systemic hypotension and decreased survival in septic dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 42 publications
(50 reference statements)
4
61
3
Order By: Relevance
“…As in humans and dogs, 4,46 an impaired cortisol response to a supraphysiologic dose (100 mg) of exogenous ACTH was significantly correlated with an increased incidence of MODS and shock in hospitalized foals, and with decreased survival in septic foals. Thus, these findings suggest that lack of an appropriate cortisol response to a supraphysiologic 100 mg dose of exogenous ACTH may identify critically ill foals with concurrent HPA axis dysfunction, even if basal cortisol concentrations are appropriately increased.…”
Section: Discussionmentioning
confidence: 94%
“…As in humans and dogs, 4,46 an impaired cortisol response to a supraphysiologic dose (100 mg) of exogenous ACTH was significantly correlated with an increased incidence of MODS and shock in hospitalized foals, and with decreased survival in septic foals. Thus, these findings suggest that lack of an appropriate cortisol response to a supraphysiologic 100 mg dose of exogenous ACTH may identify critically ill foals with concurrent HPA axis dysfunction, even if basal cortisol concentrations are appropriately increased.…”
Section: Discussionmentioning
confidence: 94%
“…The mechanism leading to relative adrenal insufficiency is not known. Most observations of this condition have been made in human beings; however, it has also been described in dogs (Burkitt et al, 2007). We are not aware of any comparable studies in wildlife or in wildlife surrogates, such as ranch mink.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings demonstrate that delta cortisol concentrations cannot be used as an isolated parameter when evaluating the ''reserve'' of the adrenal gland in acute canine illness. We would therefore argue that studies which ignored the basal cortisol concentrations when according patients the status of ''relative adrenal insufficiency'', should be viewed with caution (Burkitt et al, 2007). After many years of negating this fact and not taking basal cortisol concentrations into account when determining adrenal status, a recent publication in human critical care has shown that non-surviving patients had a lower delta cortisol than survivors.…”
Section: Discussionmentioning
confidence: 99%
“…The dearth of information on ACTH-stimulated and delta cortisol concentrations in canine critical illness has been highlighted in a recent review (Martin and Groman, 2004). A more recent study purported to document relative adrenal insufficiency in a group of critically ill septic dogs based on a dichotomized delta cortisol cutoff of 83 nmol/l (Burkitt et al, 2007). However, this study did not report the basal cortisol in non-survivors versus survivors and found no association between survival and delta cortisol when it was assessed as a continuous, non-dichotomized variable.…”
Section: Introductionmentioning
confidence: 99%